Stem Cell Therapy Used For Treatment of Heart Disease - Mahale Nikita S,; Chothave Sayali J,; Muthe Sakshi S,; Barokar Pooja G,; Kapadi Suvarna S, (Asian Journal of Pharmaceutical Research and Development, 2025)
Heart disease continues to be the foremost cause of death globally, largely due to the heart’s limited capacity for self-repair following injury. Conventional treatments, such as pharmacological therapy, mechanical support, and surgical interventions, primarily manage symptoms and slow disease progression but cannot regenerate damaged myocardium. In recent years, stem cell therapy has emerged as a promising regenerative strategy aimed at restoring cardiac structure and function. Various stem cell types—including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), and cardiac progenitor cells (CPCs)—have shown potential to promote myocardial regeneration through differentiation into cardiomyocytes, stimulation of angiogenesis, and paracrine signaling mechanisms. Preclinical studies have demonstrated improved ventricular function and reduced infarct size, while clinical trials have reported modest yet encouraging functional recovery in patients with ischemic heart disease. However, several challenges limit widespread clinical application, including poor cell survival and engraftment, immune rejection, risk of arrhythmogenesis and tumorigenicity, and ethical concerns regarding cell sources. Recent advances in tissue engineering, gene editing, and exosome-based cell-free therapies may help overcome these limitations. This review highlights the current progress, therapeutic potential, and major challenges of stem cell-based therapies in cardiac repair, emphasizing the need for standardized protocols and long-term clinical evaluation to achieve safe and effective translation into clinical practice.